1992
DOI: 10.1055/s-0038-1648493
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship Between Molecular Mass and Anticoagulant Activity in a Low Molecular Weight Heparin (Enoxaparin)

Abstract: SummaryA low molecular weight heparin (enoxaparin, mean molecular weight ~ 4,400) was separated by gel chromatography into eight different fractions with a narrow distribution around the following mean molecular weights: 1,800, 2,400, 2,900, 4,200, 6,200, 8,600, 9,800 and 11,000. We compared the influence of enoxaparin on the generation of thrombin in plasma to that of the eight fractions.We determined: a) the % of material with high affinity to antithrombin III (HAM) and the % of HAM above the critical chainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…These findings are in agreement with a recent study performed using defibrinated PPP, which also showed that inhibition of the ETP is mainly determined by the concentration of C-domain which contains the AT-binding pentasaccharide and elicits anti-FIIa activity [36]. The importance of the anti-FIIa activity of LMWHs on the inhibition of thrombin generation has also been shown in earlier studies [19,[37][38][39]. The contribution of the anti-FXa activity of LMWHs to their anticoagulant activity is still a controversial subject [40].…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in agreement with a recent study performed using defibrinated PPP, which also showed that inhibition of the ETP is mainly determined by the concentration of C-domain which contains the AT-binding pentasaccharide and elicits anti-FIIa activity [36]. The importance of the anti-FIIa activity of LMWHs on the inhibition of thrombin generation has also been shown in earlier studies [19,[37][38][39]. The contribution of the anti-FXa activity of LMWHs to their anticoagulant activity is still a controversial subject [40].…”
Section: Discussionsupporting
confidence: 92%
“…After repeated s.c. injections of IK-SSH (in group III) TFPI increased 5-to 8-fold. This is similar to results obtained with UFH [33,34] and LMWH [35,36]. TFPI also prolongs Heptest and aPTT in vitro [37].…”
Section: Discussionsupporting
confidence: 89%
“…The anticoagulant activity is 19.0 IU/mg (range 17-20; USP potency), antiFXa activity 27.7 IU/mg (range [25][26][27][28][29][30][31][32][33][34][35] and anti-FIIa activity 39.9 anti-thrombin units (ATU)/mg (range 35-60) as declared by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…The fig ures for HAM and ACLM content were obtained from previous work [11,12). Because no conclusions as to pharmacological properties should be drawn from an experiment in which each heparin was ad ministered to 1 subject only, we will not reveal the identity of the heparins.…”
Section: Methodsmentioning
confidence: 99%